Potential access to primary health care: what does the National Program for Access and Quality Improvement data show? - Severina Alice da Costa Uchôa; Ricardo Alexandre Arcêncio; Inês Santos Estevinho Fronteira; Ardigleusa Alves Coêlho; Claudia Santos Martiniano; Isabel Cristina Araújo Brandão; Mellina Yamamura; Renata Melo Maroto (Universidade de São Paulo, 2016)
Objective: to analyze the influence of contextual indicators on the performance of municipalities regarding potential access to primary health care in Brazil and to discuss the contribution from nurses working on this access. Method: a multicenter descriptive study based on secondary data from External Evaluation of the National Program for Access and Quality Improvement in Primary Care, with the participation of 17,202 primary care teams. The chi-square test of proportions was used to verify differences between the municipalities stratified based on size of the coverage area, supply, coordination, and integration; when necessary, the chi-square test with Yates correction or Fisher's exact test were employed. For the population variable, the Kruskal-Wallis test was used. Results: the majority of participants were nurses (n=15.876; 92,3%). Statistically significant differences were observed between the municipalities in terms of territory (p=0.0000), availability (p=0.0000), coordination of care (p=0.0000), integration (p=0.0000) and supply (p=0.0000), verifying that the municipalities that make up area 6 tend to have better performance in these dimensions. Conclusion: areas 4,5 and 6 performed better in every analyzed dimension, and the nurse had a leading role in the potential to access primary health care in Brazil.